Discourses on the adoption of the Barsha pump: A Q methodology study in Nepal and Indonesia - Intriago Zambrano, Juan Carlo; Diehl, Jan-Carel; Ertsen, Maurits W. (Frontiers in Sustainable Food Systems, 2022)
Improved water management is an important strategy to support smallholder farming, and thus to foster food security and improved livelihoods. Within this strategy, technologies like water pumps, especially those operating on renewable energies, are key, as they are more environmentally sound and affordable alternatives. Their successful and sustained uptake is a complex process—largely dependent on the adopter and its surrounding context—usually overlooked by traditional linear technology-transfer approaches. By means of Q methodology, we explored cross-cultural discourses around the adoption of the Barsha pump (BP), a self-reliant hydro-mechanical device that does not require any external input than flowing water to operate. We administered the method to 43 (non-)farmer respondents linked to Nepali and Indonesian smallholder farming systems. We identified three relevant discourses, one of them bipolar in nature. These three groups accounted for 39%, 36% and 28% of the total explained variance of our study. The first one identified BP’s potential early adopters. The second discourse embodied the (stereotypical) highly dependent smallholder. The last one characterized (contrasting) views around the BP as an enabler of potential service-oriented business models to achieve well-being. These results reflect the need for a shift of mindset towards new ways of understanding technological change in smallholder settings. On the one side, simplistic one-size-fits-all models cannot connect to the diversity of issues and opinions as we found. On the other side, it is virtually impossible to produce tailored solutions to satisfy each of those individual realities. We propose possible adoption pathways that may lead to the exploration of innovative and adaptable business models that serve the diversity of smallholder farming needs more effectively.